Analisis Pertumbuhan Usaha Kecil Menengah, dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Kota Batam - Intan Utna Sari; Asron Saputra (Prosiding, 2020)
One of the important benchmarks in determining the success of economic development is economic growth. The role of the government in trying to achieve development success is to determine the direction of development policy and to achieve the development goals it is necessary to have good development planning to realize stable economic growth in order to improve the welfare of the community is by improving Small And Medium Enterprises and Labor. This research aims to find out the simultaneous and partial influence of Small and Medium Enterprises, and Labor on the economic growth of Batam city. The data source is secondary data using data panels consisting of three years of time series data and cross section data of nine sub-districts that produce 45 observations. The analytical technique used to solve the problem in this study is by multiple linear regression analysis models. The results of this study show that simultaneously Small and Medium Enterprises and labor have a significant effect on economic growth in Batam City. This indicates that the number of SMEs (Small and Medium Enterprises) and labor in batam city can be the determinant of the economic growth rate in batam city. This is because SMEs and Labor are activities that can produce goods or services. In part, Small and Medium Enterprises and labor have a positive and significant effect on economic growth in Batam City, meaning that if the number of SMEs and labor is increased then economic growth will also increase.